Construcción de un banco de práctica para el estudio del ciclo de refrigeración por compresión de vapor para la sede sur de la Universidad Antonio Nariño (2021)
The project defines how the construction of a practice bench to explain the operation of the thermodynamic cycle of refrigeration by vapor compression is performed to reinforce the conceptual issue, and contribute supplanting the need that has the Antonio Nariño University in the south Bogotá headquarters, the absence of elements for practice that explain the operation of thermal cycles is performed. This document presents the construction process of the bench mentioned, from the conception of the idea to its materialization, start-up, operation tests, step by step in terms and implementation and the materials required for its construction. The results obtained will help the student to understand in a practical way the operation of the refrigeration cycle exposed. In the development of the project results of temperatures in different parts of the cycle are obtained, as well as pressures, graphs are generated where the behavior of temperatures during the operation of the refrigeration bank is analyzed, two tests are developed one with the empty compartment and the other with a thermal load in this case water at room temperature, also laboratory guides are developed and a brief introduction to SITRAD software is given.